Judges, law and war : the judicial development of international humanitarian law - Darcy, Shane (Cambridge studies in international and comparative law ;, 2014)
"International courts and judicial bodies play a formative role in the development of international humanitarian law. Judges, Law and War examines how judicial bodies have influenced the substantive rules and principles of the law of armed conflict, and studies the creation, application and enforcement of this corpus of laws. Specifically, it considers how international courts have authoritatively addressed the meaning and scope of particular rules, the application of humanitarian law treaties and the customary status of specific norms. Key concepts include armed conflicts and protected persons, guiding principles, fundamental guarantees, means and methods of warfare, enforcement and war crimes. Consideration is also given to the contemporary place of judicial bodies in the international law-making process, the challenges presented by judicial creativity and the role of customary international law in the development of humanitarian law"--